Design of a 2-Dof 8r Linkage for Transformable Hypar Structure - Korkmaz, Koray; Akgün, Yenal; Korkmaz, Koray; Maden, Feray (Taylor and Francis Ltd., 2012)
Double curved geometries including hyperbolicparaboloids (hypars) have become a trend in contemporary architecture. However, most of the constructed architectural examples of the hypars are static and cannot offer any form variability. In this paper, a 2-DOF 8R linkage mechanism is introduced to buildtransformable hypar structures. It is inspired from the basic design principles of Bennett linkage. By its distinctive connection details and additional links, this novel mechanism can change its form fromplanar geometries to various hypars. The paper begins with the brief summary of the applications of hypar structures in architecture. Secondly, main principles and deficiencies of the Bennett linkage are presented. According to these deficiencies, structural synthesis of the novel mechanism is considered. Finally, advantages and potential uses of the proposed novel mechanism are explained. © 2012 Copyright Taylor and Francis Group, LLC.
Keywords: Bennett linkage; Deployable; Kinetic architecture; Hypar; Transformation